Involuntary MDMB-4en-PINACA intoxications following cannabis consumption: clinical and analytical findings. (3rd April 2022) - Goncalves, Ruben; Labadie, Magali; Chouraqui, Simon; Peyré, Alexandre; Castaing, Nadège; Daveluy, Amélie; Molimard, Mathieu
Abstract: Background and aims: MDMB-4en-PINACA is a synthetic cannabinoid receptor agonist (SCRA) that has recently emerged. Data regarding clinical presentations in the event of intoxication is scarce. This study presents MDMB-4en-PINACA identification in cannabis consumers with clinical and analytical descriptions. Methods: Between November 2020 and March 2021, all patients with unexpected or unusually severe effects and Poisoning Severity Score (PSS) greater than or equal to 2 after cannabis consumption were included. Blood and/or urine samples were collected for toxicological analysis. When available, drug material samples were also collected for analysis. Results: Between November 2020 and March 2021, 13 patients were included. All cases typically presented with altered mental status ( n = 13), and nearly all had returned to a normal or quasi-normal state after around 11 h of observation. Neurological symptoms included headaches ( n = 3), hallucinations (3), mydriasis (3), amnesia (2) and seizures (5). Psychiatric symptoms were paranoia (6) and anxiety (2). Digestive symptoms were nausea (2) and vomiting (6). No deaths were recorded. All patients were positive for the SCRA MDMB-4en-PINACA in urine, blood and/or drug material sample. Results from toxicology testing paired with case history showed the potential for MDMB-4en-PINACA to cause or contribute to different clinical disorders. Conclusions: This study highlights the risk of intoxication by SCRAs when taking low-THC cannabis products. Forensic scientists, public health and public safety officials, law enforcement personnel and clinicians should be aware of the impact that these emergent SCRAs may have in their work, especially MDMB-4en-PINACA.